Tensile test of additively manufactured specimens with external notch removed via laser cutting in material extrusion. (June 2022) - Park, Seong Je; Lee, Ji Eun; Jin, Sun Chul; Lee, Nak-Kyu; Choi, Kyunsuk; Park, Suk-Hee; Son, Yong
Abstract: The specimens fabricated by material extrusion (ME)-type additive manufacturing (AM) have external notches because of their deposition mechanism. During tensile tests, accurate results cannot be obtained because the external notch causes stress concentration and induces fractures outside the gauge length. In this study, using laser cutting, we removed the notch of specimens without damage to the specimens. By removing the notch and stress concentration in specimens, fractures were induced within the gauge length with a 62% probability, whereas the specimens in which the notch and stress concentration were not removed had a 27% probability. Through this evaluation method, the tensile results of the specimens for various polymers can be compared fairly and quantitatively with a small standard deviation in terms of the tensile strength and elongation at break between the specimens. Highlights: Tensile test considering the external notch of the materials extrusion specimens. Remove notches using laser cutting. Minimize heat affected zone (HAZ) by establishing laser cutting conditions. Increased fracture within gauge length in tensile load via remove notch.